Study on the Drug Selection Law for Treatment of Chronic Gastritis with Spleen Deficiency and Stomach Dryness by Complex System Entropy Cluster - 史成和 王秀娟 陈建新 刘仁权 赵宇昊 杨洪军 (Journal of traditional Chinese medicine, 2010)
Objective：To study on Prof. GAO Zhong-ying＇s drug selection law for treatment of chronic gastritis with data mining technique. Methods： The 407 medical records of chronic gastritis treated by Prof. GAO Zhong-ying were collected and the study on these drugs in the recipes was carried out with data mining method. Among them, the recipe composed of one drug was studied with frequency statistical method, correlativity between drug pairs with improved mutual information, correlativity among multi-drugs with complex system entropy cluster technique. Results： In treatment of chronic gastritis by Prof. GAO Zhong-ying there were 30 drugs with a higher use frequency of over 38 times, 94 commonly-used drug pairs with correlation coefficient of over 0.05, 11 commonly-used drug core combinations. Conclusion： The results attained with data mining technique for studying experience of famous and old TCM physicians conform to the clinical practice and the method is of an important significance for summarization of famous and old TCM physicians＇ experiences.